PARTISIPASI MASYARAKAT DALAM PEMANFAATAN SAMPAH PLASTIK MENJADI PAVING BLOCK DI “UD. WONG CILIK” DESA JETIS, KECAMATAN KEMANGKON, KABUPATEN PURBALINGGA - Alifan Nurin Anamti Dieningrum; Muslihudin Muslihudin; Edy Suyanto (UNIVERSITAS SEBELAS MARET (UNS), 2020)
Participation is someone's participation in the development process either in the form of statements or in the form of activities by providing input on thoughts, energy, time, expertise, capital and material. This utilization is carried out so that the plastik waste produced can become goods that are more valuable. This study aims to determine community participation in the use of plastik waste into paving blocks at